Psikoedukasi Mengenai Pengenalan Emosi Kepada Anak-Anak Kanker di Yayasan Kasih Anak Kanker Indonesia (YKAKI) Kota Semarang - Eka Wulan Astutik; Nafadhilla Refie Anjani; Dilla Maghdalena Oktavia; Siwi Alfiana Ameli; Ardyaningtyas Dwi Lystiawaty; Muhammad Dzaki Athallah Hanan; Nabilla Nur Hanifah; Siti Hikmah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Pediatric cancer is a serious global health problem. Children with cancer often have difficulty managing emotions such as anxiety, sadness and anger. This study aims to improve the ability of children with cancer to recognize, express and manage their emotions through a psychoeducational program. Through this intervention, children are expected to develop more effective coping skills and improve their quality of life. The psychoeducation program will focus on emotion recognition through facial expressions, body language, and emotion-related vocabulary. The results of this study are expected to contribute to the development of more comprehensive psychological interventions for children with cancer.